Individual differences in a proficiency task as a function of L2 and non L2 specific dimensions - Jose Cristina M. Parina, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Research suggests that cognitive characteristics, aside from L2-specific knowledge, contribute to variation in language performance. Reading, for instance includes attitude as a very important factor and not L2-specific knowledge when determining reading ability. Research has shown that how readers extract information from the text is also proven to involve features that are not based on L2 knowledge. This paper explores how poor performance on a L2 task may be due to general language skills and other non-language specific variables. The present study employed a cross-linguistic, within-subject design that dealt with individual differences in L2 speaking via reading aloud. Results show that the highest-ranking student/s on the ITEO exam and diagnostic essay and the highest performing student based on the previous GPA were not the fastest readers, had more disfluencies, and were not able to supply all the correct words in both in L1 and L2. This shows that there are variables that affect L2 performance. This further proves that performances on L2 tasks may be more than just language concerns